Growth in the Eurozone and the Limits of Articulation of Economics and Politics in the Functionnalist Approach to European Integration - Clavé, Francis (DEMO, 2017)
This article is built up on a questioning : do not functionalism and neo-functionalism, that have strongly inspired the European construction, hamper the emergence of an articulation of the economics and the politics necessary at the present stage for the eurozone ? To answer this question three key elements of functionalism will be studied : the théorie de l'engrenage, the use of economics expertise and the will to go beyond the concept of state and sovereignty. It will be shown that the théorie de l'engrenage induces strategic noncooperative games linked to different approaches of the political economy. In order to overcome this hurdle an extensive agreement on a common economic philosophy should be reached at the least. On the other hand, the very strong primacy given to the economy and to the consumption prompts to veil the politics and has preferred the recourse to economic expertise. Finally, Mitrany's functionalism, which is very close to post-modern politics, does not allow us to think about the political aspect of the economic solutions envisaged to emerge from the crisis in the Eurozone. In particular, it does not provide a framework for articulating both the specificities of Europe facing the world and that of European countries facing Europe.(original abstract)
Keywords: Eurozone; History of European integration; Euro; Functionalism; Neofunctionalism; Political economy